2002
DOI: 10.1038/nature01339
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor α7 subunit is an essential regulator of inflammation

Abstract: Excessive inflammation and tumour-necrosis factor (TNF) synthesis cause morbidity and mortality in diverse human diseases including endotoxaemia, sepsis, rheumatoid arthritis and inflammatory bowel disease. Highly conserved, endogenous mechanisms normally regulate the magnitude of innate immune responses and prevent excessive inflammation. The nervous system, through the vagus nerve, can inhibit significantly and rapidly the release of macrophage TNF, and attenuate systemic inflammatory responses. This physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
2,602
10
61

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,907 publications
(2,753 citation statements)
references
References 25 publications
80
2,602
10
61
Order By: Relevance
“…It has already been reported that CAP interacting with α7‐nAChR expressed by macrophages and other cytokine‐producing cells15, 27, 28, 29 has markedly influenced the anti‐inflammatory response. Utilizing the major vagal neurotransmitter ACh and nicotine as AChR agonists that interact with α7‐nAChR on macrophages to reduce the release of TNF‐α and other proinflammatory cytokines confirmed that this modulation is mediated through the vagus nerve 15. Our present study demonstrated for the first time in an ICM rat model that eliciting the CAP by nicotine not only reduced the cytokines (IL‐1β, IL‐6, IFN‐γ, TNF‐α, transforming growth factor‐β) and collagens (collagen I, collagen III) of the infarction border zone but also improved the cardiac autonomic function, increased ejection fraction, and attenuated arrhythmogenic properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that CAP interacting with α7‐nAChR expressed by macrophages and other cytokine‐producing cells15, 27, 28, 29 has markedly influenced the anti‐inflammatory response. Utilizing the major vagal neurotransmitter ACh and nicotine as AChR agonists that interact with α7‐nAChR on macrophages to reduce the release of TNF‐α and other proinflammatory cytokines confirmed that this modulation is mediated through the vagus nerve 15. Our present study demonstrated for the first time in an ICM rat model that eliciting the CAP by nicotine not only reduced the cytokines (IL‐1β, IL‐6, IFN‐γ, TNF‐α, transforming growth factor‐β) and collagens (collagen I, collagen III) of the infarction border zone but also improved the cardiac autonomic function, increased ejection fraction, and attenuated arrhythmogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The constant temperature incubator was maintained (37°C) with a 95% humidified atmosphere and 5% CO 2 . Cells pretreated with nicotine (1 μmol/L) for 1 hour were stimulated with lipopolysaccharide (100 ng/mL) 15. Furthermore, to examine the effect of vagotomy, cells were treated with α‐bungarotoxin (100 mmol/L, Sigma)24 for 30 minutes before being subjected to nicotine.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence that active CHRNA7 can induce lung fibroblast and regulate lung inflammation also supports it may involve the development of both diseases. 30,31 In the current study, we found that the ≥ 4-copy of CNV-3956 that duplicates the CHRNA7 gene conferred increased risks and poor prognoses of lung cancer and COPD, underlying a possible biological mechanism by increasing CHRNA7 expression and inducing carriers to consume more cigarettes because individuals with higher CHRNA7 expressions would be more nicotine sensitive. A challenge on this mechanism is that the loss genotype of CNV-32018, which we did not test due to technical limitation, would possibly induce exon deletion of CHRNA7 and nonfunctional CHRNA7, and thus the ≥ 4-copy of CNV-3956 may cause a upregulation of nonfunctional CHRNA7.…”
Section: Discussionmentioning
confidence: 56%
“…This cranial nerve that innervates most of the peripheral organs can downregulate inflammation by decreasing the release of TNF-, IL-1, IL-6, and high-mobility group box (HMGB) 1 protein by LPS-stimulated macrophages [24]. This antiinflammatory effect is mediated by an interaction between acetylcholine, the principal neurotransmitter of the vagus nerve, and the 7-nicotinic acetylcholine receptors on macrophages [24,25]. In studies of experimental endotoxemia in rats, surgical dissection of the vagus nerve led to enhanced systemic TNF-production and accelerated the development of shock.…”
Section: Vagus Nerve and The Nicotinic Anti-inflammatory Pathwaymentioning
confidence: 99%